(untitled) (Global Journal of Management and Business Research, 2019)
From the time of Adam Smith(1776) to 2012 UNCSD Rio +20 conference we have lived in a world where government intervention in markets was not welcomed, except in very specific circumstances such as market failures, a feeling at the heart of free-market thinking. From 2012 to now June 2019, we have slowly moved to a world where permanent government intervention is not just welcomed, but also encouraged such as when governments directly intervene in markets to deal with environmental issues. This is indeed a move away from free-market thinking, and towards non-free market thinking as it represents a shift from green market solutions to dwarf green market solutions. In other words, the promotion and implementation of dwarf green market thinking like carbon pricing really require a departure from traditional economic thinking, a practice that is now accepted by today’s economists. And this raises questions such as: Has traditional economic thinking been flipped in practice when dealing with the environmental issue? If yes, what are the implications of this in terms of consumption and production in dwarf green markets? How are dwarf green markets then be expected to work?